Features of functioning paremia adjectives in the poetic work (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
This article is devoted to the functioning of paronymic attractions in the poetic text. The main functions of paronymic attractions were noticed. The examples show that, in thecontext, with the use of poetic atmosphere, associative semantic meaning is ensured at random words and consonance, which, in turn, begin to show contextual proximity, by obtaining additional connotations.
Keywords: paronymic attraction; connotation; poetic text